Answer:
Step-by-step explanation:
3x - 4y = 13 (1)
2x + y = 5 (2)
——————
3x - 4y = 13
4(2x + y = 5) (2) times 4
——————-
3x - 4y = 13
8x + 4y = 20
——————-
11x = 33
x = 33/11
x = 3
Plug x = 3 in (2):
2(3) + y = 5
6 + y = 5
y = 5-6
y = -1
Thus, x = 3 and y = -1
Answer:
In 5 years, you will have $1,288.48
Step-by-step explanation:
y = -0.60x - 4
because the slope stays the same because it is parallel and the y intercept for the new equation ends up being -4
Answer:
One of the below.
Step-by-step explanation:
12-2=10 2+x=12